Mehrsprachigkeit in der deutschsprachigen Presse des östlichen Europas / Multilingualism in the German-Language Press in Eastern Europe - Meier, Jörg (Journal für Kultur und Geschichte der Deutschen im östlichen Europa (JKGE) / Journal for Culture and History of the Germans in Eastern Europe, 2023)
From various disciplinary perspectives, this issue examines the significance and forms of multilingualism in the German-language press of Eastern Europe from the Vormärz to the eve of World War II. Linguistic practices in journalism and advertising are analyzed in terms of their methods and their goals between coexistence and competition, as well as between the mediation and demarcation of different nationalities and identities.